2015
DOI: 10.1007/s00787-015-0786-1
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentration of 25-hydroxyvitamin D in autism spectrum disorder: a systematic review and meta-analysis

Abstract: Vitamin D may play an important role in the etiology of Autism Spectrum Disorders (ASD). Vitamin D is regarded as a neuroactive steroid affecting brain development and function. It plays an essential role in myelination, which is important for connectivity in the brain. Studies have shown that decreased vitamin D levels in patients, decreased maternal vitamin D levels during pregnancy, and decreased exposure to solar UVB might increase the risk for ASD. In addition, autism symptoms and global functioning may i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 83 publications
6
95
0
4
Order By: Relevance
“…Maternal vitamin D deficiency during pregnancy and/or early childhood is considered as a possible risk factor in the development of ASD (Grant & Sole, ). In addition, another study has shown that ASD is more common in places with impaired solar UVB penetration (Wang et al., ). Considering the increasing prevalence of ASD and the promising results of our open‐label study about the role of vitamin D in autistic children (Saad, Abdel‐Rahman, et al., ), it is timely to evaluate the effect of vitamin D supplementation on ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Maternal vitamin D deficiency during pregnancy and/or early childhood is considered as a possible risk factor in the development of ASD (Grant & Sole, ). In addition, another study has shown that ASD is more common in places with impaired solar UVB penetration (Wang et al., ). Considering the increasing prevalence of ASD and the promising results of our open‐label study about the role of vitamin D in autistic children (Saad, Abdel‐Rahman, et al., ), it is timely to evaluate the effect of vitamin D supplementation on ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Another meta-analysis of 12 studies by Babaknejad et al [41] showed significantly lower zinc levels in children with ASD. Wang et al [42] performed a meta-analysis of 11 studies of the association between vitamin D and ASD. They found significantly lower levels of serum 25-hydroxy vitamin D in subjects with ASD than those in controls (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analysis studies support the involvement of particulate matter or ambient air pollution in relation to autism in North American [81,309] but not European studies [87] and for the prenatal uses of SSRI's [310] or Vitamin D deficiency in autistic patients [311] but the diverse methodologies used to measure timing and exposure have rendered clear conclusions difficult for these and others such as phthalate esters [312]. These problems are confounded by the gene/environment interactions raised in this study (i.e.…”
Section: Ecological Pollution and Bioaccumulationmentioning
confidence: 88%